2020
DOI: 10.1007/s42773-020-00061-3
|View full text |Cite
|
Sign up to set email alerts
|

Biochar amendment changed soil-bound fractions of silver nanoparticles and ions but not their uptake by radish at an environmentally-relevant concentration

Abstract: Plant uptake of silver nanoparticles (Ag NPs) and ions (Ag +) largely depends on their exchangeable and soil-bound fractions in soils, which may be influenced by biochar amendment. This study investigated the effects of biochar amendment (0.1% and 1.0%) on soil sorption of Ag NPs and Ag + , their soil-bound fractions, and their uptake and translocation by radish grown in a loamy sand soil spiked with 1 mg/kg Ag NPs or Ag +. Sorption of Ag + to the soils was much greater than that of Ag NPs, mainly because nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
(125 reference statements)
0
2
0
Order By: Relevance
“…To fractionate these metals, many authors have recognized that sequential extraction is a crucial method that could provide useful information on the bioavailability of metals and their transformation forms [ 14 , 18 , 19 , 20 ]. Although several studies confirmed that biochar is an important material for adsorbing HMs from contaminated soil, the mechanism is still unclear [ 4 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…To fractionate these metals, many authors have recognized that sequential extraction is a crucial method that could provide useful information on the bioavailability of metals and their transformation forms [ 14 , 18 , 19 , 20 ]. Although several studies confirmed that biochar is an important material for adsorbing HMs from contaminated soil, the mechanism is still unclear [ 4 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, direct uptake of the particulate form of silver has been observed in plants from a number of studies. 19,68,69 As most of the selected bioaccumulation studies didn't differentiate ionic or particulate silver in crops' edible parts, the oral RfD of silver ions and AgNPs were both considered in this risk assessment. The RfD of pristine AgNPs was adopted due to the lack of the dose response relationship of transformed AgNPs such as sulfurized AgNPs.…”
Section: Hazard Characterizationmentioning
confidence: 99%